Electronic structure and oxygen ion conductivity of as-deposited Ce0.90Sm0.10O2−δ thin film prepared by RF magnetron sputtering. (14th April 2015) - Yamaguchi, Shohei; Tasaki, Yuji; Kobayashi, Masaki; Horiba, Koji; Kumigashira, Hiroshi; Higuchi, Tohru
Abstract: The physical properties and electronic structure of Sm-doped CeO2 (Ce0.90 Sm0.10 O2−δ ) in the thin-film form have been studied. The as-deposited thin film exhibits (111) orientation on an Al2 O3 (0001) substrate. The lattice constant of the thin film is larger than that of the bulk crystal. The Ce0.90 Sm0.10 O2−δ thin film has the mixed valence states of Ce 4+ and Ce 3+ . The electrical conductivity of Ce0.90 Sm0.10 O2−δ thin film in the temperature region from 200 to 700 °C is higher than that of the undoped CeO2 thin film and is independent of the oxygen partial pressure, indicating the occurrence of high oxygen-ion conduction. The valence band consists of the O 2p state hybridized with the Ce 4f state. The 40% Ce 3+ (4f 1 L ) state in Ce0.90 Sm0.10 O2−δ thin film, which was estimated from the resonant photoemission spectra, contributes to the high oxygen-ion conduction and low activation energy.